&ccedil;&not;&not;1&ccedil;&laquo;&nbsp;(4)

# ç¬¬1ç« (4) - s>

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: s> 7¬1 Õ ˆ* ª ½ Î 1.6 ¶ h * ª æ. 1.6.1 x1 (t ) → y1 (t ) x2 (t ) → y2 (t ) x3 (t ) = x1 (t ) + x2 (t ) → y3 (t ) y3 (t ) = y1 (t ) + y2 (t ) a x4 (t ) = ax1 (t ) → y4 (t ) y4 (t ) = ay1 (t ) a 5– . • á + ªh ¶ æ . [email protected] 1 s> 7¬1 Õ x ª ½ Î* x(t ) = 0y e¸ y (t ) = 0 1.6.2 ð < ª¶ x1 (t ) → y1 (t ) x2 (t ) = x1 (t − t0 ) → y2 (t ) y2 (t ) = y1 (t − t0 ) 5– . • á + * <¶ ªð s y e¸ LTI s y[n] = 2 x[n] + 3 e ¸ ð* T ª <¶ x1[n] → y1[n] = 2 x1[n] + 3y x2 [n] → y2 [n] = 2 x2 [n] + 3 x3 [n] = x1[n] + x2 [n] → y3 [n] = 2( x1[n] + x2 [n]) + 3 ≠ y1[n] + y2 [n] [email protected] 2 s> 7¬1 Õ ¸* ª ½ Î @* ° n E Œ Ð ª %½ (¸¶ *. ª æ x[n] = 0 ) y[n] = 3 ≠ 0 % ø y x1[n] → y1[n] = 2 x1[n] + 3 x2 [n] = x1[n − n0 ] → y2 [n] = 2 x1[n − n0 ] + 3 y1[n − n0 ] = 2 x1[n − n0 ] + 3 y2 [n] = y1[n − n0 ] % ø y t y (t ) = ∫ x(τ )dτ % ø * ÷¶ ª æ . −∞ [email protected] 3 s> 7¬1 Õ x ª ½ Î* t t −∞ −∞ x1 (t ) → y1 (t ) = ∫ x1 (τ )dτ x2 (t ) → y2 (t ) = ∫ x2 (τ )dτ x3 (t ) = a1 x1 (t ) + a2 x2 (t ) → y3 (t ) = ∫ t −∞ t t −∞ [ a1 x1 (τ ) + a2 x2 (τ )] dτ −∞ y3 (t ) = a1 ∫ x1 (τ )dτ + a2 ∫ x2 (τ )dτ = a1 y1 (t ) + a2 y2 (t ) *ªΗ ¶ð 3 t x1 (t ) → y1 (t ) = ∫ x1 (τ )dτ x2 (t ) = x1 (t − t0 ) −∞ t t −∞ −∞ y2 (t ) = ∫ x2 (τ )dτ = ∫ x1 (τ − t0 )dτ = ∫ y1 (t − t0 ) = ∫ t −t0 −∞ t −t 0 −∞ x1 (λ )dλ x1 (τ )dτ = y2 (t ) . ¸ [email protected] 4 s> 7¬1 Õ À ª ½ Î* y (t ) = x(2t ) 1 m *ª8 ¶ æ . y1 (t ) = x1 (2t ) y2 (t ) = x2 (2t ) x3 (t ) = a1 x1 (t ) + a2 x2 (t ) → y3 (t ) = x3 (2t ) = a1 x1 (2t ) + a2 x2 (2t ) y3 (t ) = a1 y1 (t ) + a2 y2 (t ) 1 x1 (t ) → y1 (t ) = x1 (2t ) x2 (t ) = x1 (t − t0 ) x2 (t ) → y2 (t ) = x2 (2t ) = x1 (2t − t0 ) y1 (t − t0 ) = x1 (2(t − t0 )) = x1 (2t − 2t0 ) ≠ y2 (t ) *ª8 ¶ .æ [email protected] 5 s> 7¬1 Õ À ª ½ Î* 1.6.3¿ ð ªi ŒE*Ð@ ª ¶ ˆæe * y (t ) = 2 x(t ) + 3¶ ˆæe ª* [email protected] 6 s> 7¬1 Õ * ª ¿ Î 5– . • á + *æ ª' (¶ (æ * (¶ 'ª )æ 'ª (¶ ∆y (t ) = y2 (t ) − y1 (t ) ∆x(t ) = x2 (t ) − x1 (t ) ∆y (t ) = 2∆x(t ) *æ 'ª (¶ ∆x(t ) + H ∆y (t ) æ 'ª (¶ +H y x(t ) = 0y y (t ) = 3 ~'ª ¶ (æ * y zi (t ) = 3 = [email protected] 7 s> 7¬1 Õ ¸* ª ½ Î 1.6.4 W` 5– . • á + ªH æ &¶ y (t ) = 2 x(t ) + 3 y (t ) = x 2 (t ) y t y (t ) = ∫ x(τ )dτy y[n] = x[n] − x[n − 1]y y (t ) = x(t ) sin(t − 1) −∞ ª¶ æΗ & 1.6.5 W` 5– . • á + ªH æ &¶ [email protected] 8 s> 7¬1 Õ * ª ¿ Î y (t ) = 2 x(t − 1) y[n] = n ∑ x[k ] k =− ∞ * ª ø∋ ¶ æ ª ø∋ ¶ æ @* ª €Σ E ŒÐ k ½ y ª ø∋ ¶ æ 1 { x[n − 1] + x[n] + x[n + 1]} ª ¶ æ ø' 3 ª ¶ æ ø' y (t ) = x(−t ) y (t ) = x(t − 1) cos(t + 1) y y[n] = 1.6.6 * ª¶ æ ' *0 x1 (t ) ≠ x2 (t ) y1 (t ) ≠ y2 (t ) [email protected] 9 s> 7¬1 Õ * ª ½ Î x(t ) y (t ) = 2 y (t ) = 2 x* (tª )(æ ¶ # * ª (æ ¶ # y (t ) = sin x(t ) x2 (t ) x1 (t ) + 2π x2 (t ) ≠ x1 (t ) y2 (t ) = y1 (t ) y (t ) = sin x(ª t ¶ )(æa * [email protected] 10 s> 7¬1 Õ ˜* ª ½ Î * )¶ æ ª y (t ) = x(t − t0 ) y (t ) = x(t + t0 ) dx(t ) y (t ) = dt t y (t ) = ∫ x(τ )dτ −∞ y[n] = n ∑ x[k ] y[n] = x[n] − x[n − 1] y k =− ∞ 1.6.7 ª¶ æ) [p VH BIBO [p ª¶ æ) x(t ) < M in [email protected] y (t ) < M out 11 s> 7¬1 Õ * ª ½ Î 5– . • á + ªÈæ \$¶ s y (t ) = x (t )s y (t ) = e s y (t ) = tx(t )s y[n] = 2 x (t ) n ∑ x[k ] k =− ∞ s y (t ) = x 2 (t )s x(t ) < Ms y (t ) < M 2È\$æ ª¶ y (t ) = e x ( t ) x(t ) < M y (t ) < e M ∪¶ ª \$æ s x(t ) = u (t )s x(t ) ≤ 1s y (t ) = tu (t* )È\$æ ª¶ [email protected] 12 s> 7¬1 Õ ¸* ª ½ Î * ª -¨ æ ¶ P26 s 1.4(a)(e) P28 s 1.18 P26 s 1.5(2)(3) P28 s 1.19 P26 s 1.6 P26 s 1.7(2)(3)(4) P26 s 1.9 P27 s 1.11(1)(2)(5)(6) P27 s 1.14 [email protected] 13 ...
View Full Document

## This note was uploaded on 08/22/2011 for the course EE 201 taught by Professor Yhm during the Spring '05 term at Zhejiang University.

Ask a homework question - tutors are online